Pengaruh Tindak Tutur Guru terhadap Berpikir Kritis Siswa Sekolah Dasar dalam Pembelajaran - Alifiya Zhafira; Melva Zainil (CV. ITTC INDONESIA, 2025)
This study aims to explore the influence of teacher speech acts on students' critical thinking skills in elementary schools during the learning process. Speech acts, as a means of verbal communication, have an important role in supporting students' cognitive development. The method used is the Systematic Literature Review (SLR), by collecting data from five accredited national journal articles. The results of the analysis show that the use of various types of speech acts locutionary, illocutionary, and perlocutionary significantly affects students' understanding and engagement. Locutionary acts help students understand basic materials, while illocutionary and perlocutionary acts encourage active participation and create emotional responses. These findings emphasize the importance of teacher training that focuses on effective communication skills to improve the quality of education and prepare students to become critical thinkers.